FACILITATION OF HALAL CERTIFICATION THROUGH THE SELF-DECLARE MECHANISM FOR MSMEs/IKM IN WONOSOBO DISTRICT - Junaidi, Mahfudz; Puwanto, Hery; Irvan Fuadi, Salis; Suyud Elsyam, Robingun (LPPM Univ. Ibn Khaldun Bogor, 2022)
Indonesia is a very promising area for the global market and instruments are needed to protect domestic products. So there needs to be a guarantee of comfort for consumers and producers. Through the strategy of facilitating halal certification activities by UHC, it was concluded: that the facilitation of halal certification through the self-declaring mechanism is a technical assistance activity for SMEs or IKM actors in the Wonosobo district to obtain halal certification, including business identification numbers (NIB). The output of this facilitation is beneficial for MSMEs/IKMs to increase awareness of the importance of halal and halal-certified products, as a step to protect consumers and better marketing branding, and have an impact on strengthening public trust.